Оценка пропускной способности энергетического канала по показателям мгновенной мощности в задачах электромеханики - Загирняк, М.В.; Родькин, Д.И.; Коренькова, Т.В. (Технічна електродинаміка, 2012)
It has been shown that the analysis of power conversion processes in all the power structure elements, based on instantaneous power components, underlies the estimation power channel of electromechanical systems carrying capacity. Presence of power variable component reflecting energy exchange processes in the system results in the decrease of the carrying capacity of the object power channel. It has been established that effective power is a quality measure for power processes in the system. An index of system power controllability has been offered. An index of power channel carrying capacity has been offered.